VEHICLE PARKING PERFORMANCE ANALYSIS OF MARKETS IN DUREN SAWIT SUBDISTRICT - Irnanda Satya Soerjatmodjo; Andika Setiawan; Alfian Dwi Indrianto; Trijeti Trijeti; Tanjung Rahayu (University Muhammadiyah Jakarta, 2025)
Traditional markets are characterized by direct retail transactions between sellers and buyers, operating on either a temporary or permanent basis with specific service levels. Perumnas Klender Market represents one of the prominent traditional markets in Jakarta. High levels of commercial activity during peak hours frequently result in significant vehicle accumulation within the market's parking facilities. Consequently, parking management has become a critical factor in maintaining the functionality of traditional market infrastructure. This research aims to evaluate the parking characteristics and performance for motorcycles and private vehicles. Primary data were collected through field surveys and analyzed using the parking characteristic formulations established by the Directorate General of Land Transportation’s technical guidelines. The findings indicate that the current parking area is insufficient to accommodate the volume of vehicles, primarily due to limited space and irregular parking behavior among visitors. Analytical results show a parking index exceeding 100%, signifying that vehicle demand surpasses the available capacity. By implementing the proposed alternatives, the parking index can be effectively reduced to a more sustainable level.Keywords: Traditional Market, Parking Performance, Parking Index, Parking Characteristics, Parking Accumulation